2010
DOI: 10.1590/s0066-782x2010005000021
|View full text |Cite
|
Sign up to set email alerts
|

Filtração glomerular e fatores associados em hipertensos atendidos na atenção básica

Abstract: Background: In Brazil, arterial hypertension (AH) constitutes one of the main risk factors for chronic kidney disease (CKD). The monitoring of glomerular filtration (GF) is recommended for the assessment of kidney function in hypertensive individuals, as GF decrease precedes symptom onset.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0
7

Year Published

2012
2012
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 30 publications
1
3
0
7
Order By: Relevance
“…This study inves gated the risk factor of overweight/ obesity and its prevalence, which was observed in more than half of the pa ents, as well as its sta s cal associaon with Groups A and C. A study was performed with 675 hypertensive pa ents with and without diabetes registered in the HYPERDIA program at a Health Center in São Luís, MA, which detected a higher prevalence of individuals with a diagnosis of being overweight (38.0%) and obese (27.0%) (14) . A similar prevalence of excessive weight was found in hypertensive subjects from another study, with 75.4% of the subjects being overweight or obese (15) .…”
Section: Discussionmentioning
confidence: 99%
“…This study inves gated the risk factor of overweight/ obesity and its prevalence, which was observed in more than half of the pa ents, as well as its sta s cal associaon with Groups A and C. A study was performed with 675 hypertensive pa ents with and without diabetes registered in the HYPERDIA program at a Health Center in São Luís, MA, which detected a higher prevalence of individuals with a diagnosis of being overweight (38.0%) and obese (27.0%) (14) . A similar prevalence of excessive weight was found in hypertensive subjects from another study, with 75.4% of the subjects being overweight or obese (15) .…”
Section: Discussionmentioning
confidence: 99%
“…Nesse sentido, ambas as fórmulas devem ser usadas com precaução, principalmente em subgrupos de pacientes que não foram incluídos nos estudos originais (Cocrockft-Gault e MDRD), como crianças, idosos, obesos, desnutridos, gestantes, pacientes com doença hepática e aqueles que realizaram transplante renal. Todavia, essas fórmulas são validadas e empregadas para identificar alteração da filtração glomerular, principalmente em pacientes com fatores de riscos para o desenvolvimento de doença renal, como os hipertensos (17) .…”
Section: Métodounclassified
“…Reitera-se que, neste estudo, a prevalência de FG estimada estava reduzida para 20,6% dos participantes, sendo a FG 30 a 59 ml/min em 19,0% e a FG 29 a 15ml/min em 1,6% da amostra compatível com lesão renal com insuficiência moderada e severa, respectivamente. Esses dados são semelhantes a estudo nacional (17) que avaliou a FG, com método padrão ouro, em hipertensos, usando o clearance de 24 horas e mostrou prevalência de FG reduzida em torno de 24,6%.…”
Section: Métodounclassified
See 1 more Smart Citation
“…Many studies have found that excess weight and abdominal fat are risk factors for Revista de Nutrição http://dx.doi.org/10.1590/1678-98652016000200005 CKD [8][9][10][11] . Abdominal obesity, one of the components of the metabolic syndrome, dramatically increases the rates of metabolic, cardiovascular, and renal diseases globally 12 .…”
Section: Introductionmentioning
confidence: 99%